Suppression of Arbuscule Degeneration in Medicago truncatula phosphate transporter4 Mutants Is Dependent on the Ammonium Transporter 2 Family Protein AMT2;3. Issue 4 (3rd April 2015) - Breuillin-Sessoms, Florence; Floss, Daniela S.; Gomez, S. Karen; Pumplin, Nathan; Ding, Yi; Levesque-Tremblay, Veronique; Noar, Roslyn D.; Daniels, Dierdra A.; Bravo, Armando; Eaglesham, James B.; Benedito, Vagner A.; Udvardi, Michael K.; et al.
Abstract : Analyses of phosphate and ammonium transporter mutants reveal differential requirements for these proteins during arbuscular mycorrhizal symbiosis depending on the plant nutrient status. Abstract: During arbuscular mycorrhizal (AM ) symbiosis, the plant gains access to phosphate (Pi) and nitrogen delivered by its fungal symbiont. Transfer of mineral nutrients occurs at the interface between branched hyphae called arbuscules and root cortical cells. In Medicago truncatula, a Pi transporter, PT4, is required for symbiotic Pi transport, and in pt4, symbiotic Pi transport fails, arbuscules degenerate prematurely, and the symbiosis is not maintained. Premature arbuscule degeneration (PAD ) is suppressed when pt4 mutants are nitrogen-deprived, possibly the result of compensation by PT8, a second AM -induced Pi transporter. However, PAD is also suppressed in nitrogen-starved pt4 pt8 double mutants, negating this hypothesis and furthermore indicating that in this condition, neither of these symbiotic Pi transporters is required for symbiosis. In M. truncatula, three AMT2 family ammonium transporters are induced during AM symbiosis. To test the hypothesis that suppression of PAD involves AMT2 transporters, we analyzed double and triple Pi and ammonium transporter mutants. ATM2;3 but not AMT2;4 was required for suppression of PAD in pt4, while AMT2;4, but not AMT2;3, complemented growth of a yeast ammonium transporter mutant. In summary, arbuscule life span is influenced by PT4 and ATM2;3, and their relative importance varies with the nitrogen status of the plant.